Pre-Service English Teachers’ Narrative Identity - ULUM, Ömer Gökhan (Journal of Education Culture and Society, 2020)
Aim. This phenomenological study probes the experiences of pre-service English as Foreign Language (EFL) teachers in the practicum process. Thus, this paper aims at bringing a light to the effects of practicum experiences of pre-service EFL teachers on their professional identity. Methods. Based upon a narrative identity method, this phenomenological inquiry examines the experiences of pre-service EFL teachers (N= 20) in their practicum. A one-shot question was directed to the informants with the aim of clarifying their personal constructs. Results. Practicum has got a significant role in education faculties all over the world. The theories applied in teaching practicum are quite common and universal. However, the practices utilised in practicum may show variations among education faculties. Further, the practicum content, and the characteristics of teacher candidates and supervisors may cause practicum to be carried out in diverse ways. The practicum aspect of pre-service teacher education is contemporarily given significant emphasis all around the world. Further, the exact theory of practicum and the desired outcomes of the related practices are relatively identical in education faculties throughout the world. Nonetheless, the practicum practices represent diversities among institutions. Yet, the characteristics and experiences of pre-service teachers may lead the practicum to be carried out in diverse ways in dissimilar contexts. Conclusion. The results of the study suggest that teacher candidates developed both positive and negative cognitive constructs during their practicum. Related implications are provided to overcome the problems encountered during practicum, as well as to suggest ways to develop EFL pre-service teachers’ practicum process. Keywords: EFL teachers, pre-service EFL teachers, practicum, narrative identity, professional identity